2012
DOI: 10.1111/j.1469-1795.2012.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

High levels of population differentiation in Eurasian lynx at the edge of the species' western range in Europe revealed by mitochondrial DNA analyses

Abstract: Large terrestrial carnivores are particularly prone to factors constraining levels of population genetic diversity because of their low densities and high spatial requirements. We studied the pattern of Eurasian lynx Lynx lynx population genetic variability in the westernmost part of its natural range from Scandinavia to the Carpathian Mountains (north-central Europe) based on 190 samples using 613 base pair-long sequences from the mitochondrial DNA control region (mtDNAcr). We examined whether the population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 33 publications
5
36
1
Order By: Relevance
“…In contrast, the bobcat, Canada, and Eurasian lynx, based on mtDNA and microsatellites have shown moderate levels of genetic diversity and little genetic structure across most of their ranges [39, 43, 44]. Hence, the Lynx genus arises as a good model to study patterns of functional genetic variation following extreme overall genetic erosion.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the bobcat, Canada, and Eurasian lynx, based on mtDNA and microsatellites have shown moderate levels of genetic diversity and little genetic structure across most of their ranges [39, 43, 44]. Hence, the Lynx genus arises as a good model to study patterns of functional genetic variation following extreme overall genetic erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Such population sinks may effectively reduce the dispersal rate of lynx and thus the gene flow between neighbouring populations inhabiting different forest patches. Indeed, based on mtDNA haplotype frequencies, it was found that the lynx population from the BPF was significantly divergent from neighbouring populations (Ratkiewicz et al 2012). Furthermore, it was characterised by a relatively low allelic richness (Schmidt et al 2009) when compared to Latvian and Estonian lynx which populate more continuous habitats.…”
Section: Periodmentioning
confidence: 99%
“…The ranging and dispersal routes of lynx have been shown to be dependent on the distribution and availability of woodlands Schmidt 1998;Podgórski et al 2008). Recent studies on lynx genetic diversity and differentiation have suggested that closely situated but isolated populations are poorly connected through contemporary gene flow (Schmidt et al 2009(Schmidt et al , 2011Ratkiewicz et al 2012), indicating the possible effect of habitat fragmentation on the effectiveness of lynx dispersal. Studies in Scandinavia have shown that human-induced factors (harvest, poaching, vehicle collisions) are the chief mortality causes in this species (Andrén et al 2006) and that human-dominated areas represent a potentially high mortality risk for the lynx (Bunnefeld et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While lynx have been successfully reintroduced to several areas of central and western Europe (Kaczensky et al, 2013), habitat availability and human-carnivore conflict continue to be critical barriers to their success in many areas. As a result, habitat constraints and limited connectivity between Eurasian lynx populations have resulted in high levels of genetic differentiation in parts of their western range (Ratkiewicz et al, 2012). In some cases, isolated populations have been recognized as subspecies of lynx, leading to the designation of discrete, demographically independent populations.…”
mentioning
confidence: 99%